Nutritional importance of vitamin D in the prevention of COVID-19: a systematic review (Research, Society and Development, 2021)
Objective: To verify the nutritional importance of vitamin D in the prevention of Covid-19. Methodology: A systematic review was carried out which followed the PRISMA criteria – Main Items for Reporting Systematic Reviews and Meta-analysis. The search for articles was performed in the PubMed, Scielo, Lilacs and Virtual Health Library databases, using the descriptors in Portuguese and English: COVID-19", "Prevention" and "Vitamin D". Access to the databases was carried out from February to March 2021. Results: 250 articles were found and after applying the inclusion criteria, 13 articles remained. Vitamin D was found to play an important role in decreasing the risks and severity of COVID-19. The possible explanation for the mechanism of action of this vitamin in infectious diseases such as COVID-19 is its regulatory role in acquired immunity and innate immunity. Conclusion: Vitamin D may play a role in preventing COVID-19, particularly for people with levels below recommended levels. It is linked to anti-inflammatory, antiviral, antithrombotic, antioxidant and immune system modulating actions as being of great value in decreasing the risk of infection and disease progression.